A variable-order fractional proportional-integral controller and its application to a permanent magnet synchronous motor - Chen, Liping (2021)
The time-domain approximation of the Grünwald–Letnikov fractional derivative is intuitive and widely adopted in the design of fractional-order proportional-integral (FOPI) controllers. To solve the accuracy reduction caused by truncating the series, an optimized discrete FOPI is presented. The effectiveness of the new FOPI is highlighted and compared with the one exhibited by a controller implemented based on the Oustaloup method. Furthermore, to improve the performance of the FOPI, a variable-order fractional proportional-integral (VFPI) controller is proposed. The response of the VFPI is verified in the control of a permanent magnet synchronous motor. Simulation and experimental results show the superior performance of the VFPI.